Septik Tank Komunal sebagai Sumber Daya Bersama dalam Upaya Memelihara Lingkungan - Mila Mardotillah; Rini Soemarwoto (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2019)
Domestic waste is one of the pollutant in the environment, especially water sources. Disposal waste without processing and population growth affects the waste disposal. The community must obliged to manage domestic waste as an effort to protect the environment. The aim of this study was to determine the success of the community in managing communal septic tanks as a shared resource in managing domestic wastes. This research uses descriptive qualitative method by taking the case in RW 05, Cigadung Village, Bandung City. Communal septic tank is an facility that can accommodate high volume of domestic wastes. The existence of communal septic tanks is not easy considering the public does not understand the workings of communal septic tanks. The existence of communal septic tanks and their sustainability is much determined by the community leader and the government as facilitators. The role of kinship has an important meaning in solving problems in the community. Water resources are maintained from the local values to the maintenance of communal septic tanks as a shared resource, are carried out by community social organizations through overall collaboration in the activities of the posyandu, RW and other community activities through facilitation of the local government.